ENZYMATIC AND NON-ENZYMATIC ANTIOXIDANT PROPERTIES OF Tylophora pauciflora Wight and Arn. – AN IN VITRO STUDY - Starlin, Thangarajan; Gopalakrishnan, Velliyur Kanniappan (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objectives: Many oxidative stress related diseases are as a result of accumulation of free radicals in the body. A lot of researches are going on worldwide directed towards finding natural antioxidants of plants origins. In this study, we assessed enzymatic and non-enzymatic antioxidant properties of Tylophora pauciflora. Method: The enzymatic antioxidants (Superoxide dismutase, Catalase, Glutathione-s-transferase, Glutathione peroxidase, Peroxidase, Ascorbate oxidase and Polyphenoloxidase) and non-enzymatic antioxidants (Total reduced glutathione and Vitamin C) activities were determined. Results: The present study revealed that Tylophora pauciflora has an excellent source of enzymatic and non-enzymatic antioxidants. Conclusion: The present study, results has capability to scavenge the free radicals and protect against oxidative stress causing diseases. In future Tylophora pauciflora may serve as a good pharmacotherapeutic agent. Keywords: Tylophora pauciflora, enzymatic antioxidants, Non-enzymatic antioxidants, Oxidative stress, Free radicals